DETERMINANTS OF CUSTOMER DECISIONS TO SAVE AT ISLAMIC BANKS - Buono, Kulup Bina; Suryanto, Tulus (Sharia Business Management UIN Raden Intan Lampung, 2022)
The purpose of this study is to analyze the factors that determine the level of trust and public interest in saving savings in Islamic banks. This study uses a qualitative method through a multi-dimensional approach and the type of data used in this study is secondary data obtained through literature reviews of previous scientific studies, bank reports, independent agency reports, and online media. Researchers found that the level of inclusion and literacy of Islamic financial institutions affects consumer decisions to save their money in Islamic banks. Building customer loyalty and emotional bonds is needed in order to raise the image and make free marketing with testimonials for their satisfaction as customers.